TLR2 engagement on CD4+ T cells enhances effector functions and protective responses to Mycobacterium tuberculosis. Issue 5 (14th March 2014) - Reba, Scott M.; Li, Qing; Onwuzulike, Sophia; Ding, Xuedong; Karim, Ahmad F.; Hernandez, Yeritza; Fulton, Scott A.; Harding, Clifford V.; Lancioni, Christina L.; Nagy, Nancy; Rodriguez, Myriam E.; Wearsch, Pamela A.; et al.
<x xml:space="preserve">Abstract</x> We have previously demonstrated that mycobacterial lipoproteins engage TLR2 on human CD4+ T cells and upregulate TCR‐triggered IFN‐γ secretion and cell proliferation in vitro. Here we examined the role of CD4+ T‐cell‐expressed TLR2 in Mycobacterium tuberculosis (MTB) Ag‐specific T‐cell priming and in protection against MTB infection in vivo. Like their human counterparts, mouse CD4+ T cells express TLR2 and respond to TLR2 costimulation in vitro. This Th1‐like response was observed in the context of both polyclonal and Ag‐specific TCR stimulation. To evaluate the role of T‐cell TLR2 in priming of CD4+ T cells in vivo, naive MTB Ag85B‐specific TCR transgenic CD4+ T cells (P25 TCR‐Tg) were adoptively transferred into Tlr2−/− recipient C57BL/6 mice that were then immunized with Ag85B and with or without TLR2 ligand Pam3Cys‐SKKKK. TLR2 engagement during priming resulted in increased numbers of IFN‐γ‐secreting P25 TCR‐Tg T cells 1 week after immunization. P25 TCR‐Tg T cells stimulated in vitro via TCR and TLR2 conferred more protection than T cells stimulated via TCR alone when adoptively transferred before MTB infection. Our findings indicate that TLR2 engagement on CD4+ T cells increases MTB Ag‐specific responses and may contribute to protection against MTB infection.